Bidirectional two-sample Mendelian randomization analysis identifies protein C rather than protein S or antithrombin-III as associated with deep venous thrombosis - Liang Shu; Liyan Sun; Cong Yu; Dabin Ren; Yisong Zhang; Ping Zheng (Archives of Medical Science)
Introduction Observational studies have indicated significant contributions of protein C and protein S to thrombotic diseases, yet the “anticoagulation paradox” in deep venous thrombosis (DVT) remains unresolved. Therefore, we conducted an investigation to discern the causal effects of protein C, protein S and antithrombin-III on DVT risk.